Representasi Nilai Edukatif Pada Karakter Anak dalam Konten YouTube Kimbab Family - Aryo Lintang Bimo , Yafi'; Zulaikha; Sugeng Widiarto , Didik (KOMUNIKA, 2026)
The development of digital media, especially YouTube, should be able to become a place for conveying information as well as learning and also to provide positive show for audience, one of wich Kimbab Family YouTube content. That family content present positive activities between parents and children. The purpose of this study is to analyze and describe the Kimbab Family YouTube content by selecting content that representation educative value on child character using Roland Barthes' semiotics. This study uses a qualitative approach with a case study method against three videos that show the daily activities of the children. Data collection was carried out through observation and documentation, which was then analyzed descriptively. The results show that family content represents educative values through children's characters who are communicative, help each other and cooperation, as well as brave and independent. Communicative are displayed through the children interactions with people you just met, with feel politely and actively respond through two-way communication. Mutual assistance and cooperation are displayed when family members are each compact and help another at the timewhen doing something together. brave and independent are displayed shown through children who are given trust by their parents to try new things independently without supervision. This research provides conclusions that Kimbab Family YouTube content has the potential to be inspiring and usefull content, as well as the children characters shown are able to be good examples in learning children's character in this modern era.